Cognitive Emotion Regulation Strategies Associated With the DSM‐5 Posttraumatic Stress Disorder Criteria. Issue 4 (30th June 2017) - Kaczkurkin, Antonia N.; Zang, Yinyin; Gay, Natalie G.; Peterson, Alan L.; Yarvis, Jeffrey S.; Borah, Elisa V.; Dondanville, Katherine A.; Hembree, Elizabeth A.; Litz, Brett T.; Mintz, Jim; Young‐McCaughan, Stacey; Foa, Edna B.; et al.
Abstract : Maladaptive cognitive emotion regulation strategies have been proposed to contribute to the maintenance of posttraumatic stress disorder (PTSD). Prior work has focused on the relationship between these strategies and PTSD as a whole, rather than on how they are related to each PTSD symptom cluster. The purpose of the current study was to determine whether cognitive emotion regulation strategies are predictive of certain PTSD symptom clusters under the Diagnostic and Statistical Manual of Mental Disorders 5th ed. ( DSM‐5 ; American Psychiatric Association, 2013) criteria (intrusive thoughts, avoidance, negative alterations in cognitions and mood, and hyperarousal). Participants included 365 treatment‐seeking, active‐duty military personnel with PTSD. The negative alterations in cognitions and mood cluster were associated with dysfunctional cognitions: greater negative cognitions about the self, negative cognitions about the world, and self‐blame, as well as catastrophizing ( R c 2 = .519). The negative alterations in cognitions and mood cluster did not show a strong relationship with blaming others, possibly due to the complex nature of self‐ and other‐blame in this primarily deployment‐related PTSD sample. Finally, the intrusive thoughts cluster was associated with catastrophizing ( R c 2 = .211), suggesting an association between frequent intrusive memories and excessively negative interpretation of those memories.